(untitled) (Международный научный журнал «Инженер», 2026)
The paper investigates the influence of a truncated conical elastomeric element embedded in a bearing support on the vibrational behavior of a rotor system. A dynamic model of the “rotor–bearing–support” system is considered, taking into account the elastic and damping properties of the elastomeric layer and the asymmetry of the rotor’s center of mass. Based on Lagrange’s equations of the second kind, an equation of forced vibrations is obtained, and numerical modeling of amplitude–frequency and transient characteristics is performed. It is shown that the use of a conical elastomer leads to a reduction in resonance amplitudes, a shift in the critical frequency, and an increase in the dynamic stability of the system.